Rafael Rachel Neis, When a Human Gives Birth to a Raven: Rabbis and the Reproduction of Species - Ahuvia, Mika (Journal for the study of religion, nature and culture, 2024)
Rafael Rachel Neis, When a Human Gives Birth to a Raven: Rabbis and the Reproduction of Species (Oakland: University of California Press, 2023), 289 pp., $34.95 (pbk), ISBN: 9780520391192.